Hello there.
Explanation:
↓↓↓↓↓↓↓↓↓↓
![4-(2x-3)=3](https://tex.z-dn.net/?f=4-%282x-3%29%3D3)
First, subtract by 4 from both sides.
![4-(2x-3)-4=3-4](https://tex.z-dn.net/?f=4-%282x-3%29-4%3D3-4)
Second, simplify.
![-(2x-3)=-1](https://tex.z-dn.net/?f=-%282x-3%29%3D-1)
Third, divide by -1 from both sides.
![\frac{-(2x-3)}{-1}=\frac{-1}{-1}](https://tex.z-dn.net/?f=%5Cfrac%7B-%282x-3%29%7D%7B-1%7D%3D%5Cfrac%7B-1%7D%7B-1%7D)
Fourth, simplify.
![2x-3=1](https://tex.z-dn.net/?f=2x-3%3D1)
Next, add by 3 from both sides.
![2x-3+3=1+3](https://tex.z-dn.net/?f=2x-3%2B3%3D1%2B3)
Then simplify.
![2x=4](https://tex.z-dn.net/?f=2x%3D4)
Therefore, divide by 2 from both sides.
![\frac{2x}{2}=\frac{4}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3D%5Cfrac%7B4%7D%7B2%7D)
Finally, simplify.
![x=2](https://tex.z-dn.net/?f=x%3D2)
<u><em>Answer⇒⇒⇒⇒x=2</em></u>
Hope this helps!
Thank you for posting your question at here on Brainly.
-Charlie
Answer:
245,000 is the answer please give brainliest
Step-by-step explanation:
17+26 is different from 36+53 by if you add 17+26 the sum would be 43. And if you add 36+53 the sum would also be 89. So that means the way how they are different is that the 17+26 and 36+53 has different kinds of sums. They have different kinds of sums because you are different numbers.
Hope this helped and if you need more help then just message me instead :)
Hello,
(10-4x²)-(7x+?)=3x-6x²
==>10-4x²-7x-3x+6x²=?
==>?=2x²-10x+10